Evaluation of Mitotic Figures and Cellular and Nuclear Morphometry of Various Histopathological Grades of Oral Squamous Cell Carcinoma: Comparative study using crystal violet and Feulgen stains - Kesarkar, Kashmira (Sultan Qaboos Univ Med J, 2018)
OBJECTIVES: The objectives of this study were to quantitatively estimate the number of mitotic figures (MFs) and evaluate the cellular and nuclear features of various histological grades of oral squamous cell carcinoma (OSCC) using Feulgen and 1% crystal violet stains. METHODS: This case-control study took place at the Dr D. Y. Patil Dental College & Hospital in Mumbai, Maharashtra, India, between June and December 2016. A total of 51 samples were retrieved from the hospital archives. Of these, 15 well-differentiated, 15 moderately-differentiated and six poorly-differentiated OSCC samples formed the case group while 15 samples of normal gingival mucosa constituted the control group. Each sample was dyed using Feulgen and 1% crystal violet stains and the mitotic count, nuclear area (NA), cellular area (CA), nuclear perimeter (NP), cellular perimeter (CP) and nuclear-to-cytoplasmic (N/C) ratio was calculated using computer-aided morphometry techniques. RESULTS: The number of MFs visible per field was significantly higher in Feulgen-stained sections as compared to those stained with crystal violet (P = 0.050). In addition, the NA, NP, CA and CP values and N/C ratios of samples in the experimental group increased significantly in accordance with an increase in OSCC grade (P <0.001). CONCLUSION: The Feulgen stain is more reliable than 1% crystal violet in terms of the selective staining of MFs. Moreover, the findings of this study indicate that computer-based morphometric analysis is an effective tool for differentiating between various grades of OSCC.